2017
DOI: 10.1002/smll.201702664
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Dioxide Coated WS2@Fe3O4/sSiO2 Nanocomposites for pH‐Responsive MR Imaging and Oxygen‐Elevated Synergetic Therapy

Abstract: Recently, the development of multifunctional theranostic nanoplatforms to realize tumor-specific imaging and enhanced cancer therapy via responding or modulating the tumor microenvironment (TME) has attracted tremendous interests in the field of nanomedicine. Herein, tungsten disulfide (WS ) nanoflakes with their surface adsorbed with iron oxide nanoparticles (IONPs) via self-assembly are coated with silica and then subsequently with manganese dioxide (MnO ), on to which polyethylene glycol (PEG) is attached. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 66 publications
2
73
0
Order By: Relevance
“…[11,13,16] Unfortunately,e ither the lack of controllability or the presence of phototoxicity accompanied by the limited penetrability troublesomely hinders the practical utility.B yc omparison, the endogenoust riggering of CO release by the tumor microenvironment (TME, such as acidity, redox property,o ver-expressed H 2 O 2 )i ss uperioro wing to no limitation of the penetration depth,a nd am ore focused and tumor-specific CO release, [17,18] but there has not been ar elated breakthrough so far.M oreover,t he integration of TME-responsived rugs with advanced nanocarriersi sa lso highly desired to achieveatargeted delivery,c ontrolled release, and release monitoring forC Ot herapy of cancer. [19] Amongavariety of nanocarriers, metal-organic frameworks (MOFs) have recently emerged as promising porousc rystalline materials because of their ultrahighs urface area, tunable cavities, and tailorable chemistry. [20][21][22][23] In particular, the designable fluorescent ligands of the MOF provides everal advantages in luminescent sensors and biological imaging, and allow to improvec oordinated interactions for alterablefluorescenceproperties.…”
Section: Introductionmentioning
confidence: 99%
“…[11,13,16] Unfortunately,e ither the lack of controllability or the presence of phototoxicity accompanied by the limited penetrability troublesomely hinders the practical utility.B yc omparison, the endogenoust riggering of CO release by the tumor microenvironment (TME, such as acidity, redox property,o ver-expressed H 2 O 2 )i ss uperioro wing to no limitation of the penetration depth,a nd am ore focused and tumor-specific CO release, [17,18] but there has not been ar elated breakthrough so far.M oreover,t he integration of TME-responsived rugs with advanced nanocarriersi sa lso highly desired to achieveatargeted delivery,c ontrolled release, and release monitoring forC Ot herapy of cancer. [19] Amongavariety of nanocarriers, metal-organic frameworks (MOFs) have recently emerged as promising porousc rystalline materials because of their ultrahighs urface area, tunable cavities, and tailorable chemistry. [20][21][22][23] In particular, the designable fluorescent ligands of the MOF provides everal advantages in luminescent sensors and biological imaging, and allow to improvec oordinated interactions for alterablefluorescenceproperties.…”
Section: Introductionmentioning
confidence: 99%
“…W‐based nanomaterials also hold the great attention in radiosensitization field in recent years . For example, Yong et al reported a new ultrasmall bovine serum albumin (BSA)‐coated GdW 10 O 36 nanoclusters (GdW 10 @BSA NCs) as radiosensitizers for RT treatment .…”
Section: General Strategies Of Nanomaterial‐mediated Tumor Radiosensimentioning
confidence: 99%
“…Therefore, when combing PTT with RT, the heat generated from PTT can elevate the oxygen level in cancer cells to make the cells more sensitive to radiation, and thus the RT therapeutic effect is availably strengthened. Up to date, a large number of literatures about PTT and RT synergetic therapy can be searched . And we roughly summarized the evolution trends of this synergetic strategy as follows.…”
Section: General Strategies Of Nanomaterial‐mediated Tumor Radiosensimentioning
confidence: 99%
“…Severald ifferent substrates have been proposed as "reducing" agentsf or permanganate, from classic reducing agents such as sodium borohydrate (NaBH 4 ), [50] to green alternatives already described for other nanotechnology applications( e.g.,g lucose), [51,52] to polymers with reducing properties (PAH, poly allylamine hydrochloride, [32,53] polyvinylpyrrolidonep lus polyacrylic acid (PAA) [31] )o rt ob iological/biochemicalm olecules (proteins such as bovine serum albumin (BSA), [54] or buffers like 2-(N-morpholino)ethanesulfonic acid (MES)). [55] Anothers trategy,f ollowedp articularly when the objective is to grow MnO 2 on top of another structure, is to use unreacted/partially reacted materials from previouss teps of the synthesis, to reduce KMnO 4 .F ollowing this strategy,M nO 2 has been grown on top of SiO 2 nanoparticles (or SiO 2 shells)b y using partially reacted silaneso nt he surface of the nanoparticles (Figure2E), [45,[56][57][58][59] and MnO 2 nanosheets were grown on gold nanostars by using unreacted HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) from the preparation of the nanostars. [60] Similarly,n anostructures with redox properties can also be used to reduce the permanganate precursor to MnO x nanostructures.…”
Section: Manganese Oxidesmentioning
confidence: 99%